Customer Satisfaction Based on Marketing Mix Strategy (7P) at PT Tirta Perkasa Sejahtera Bondowoso - Cahyono, Inge Cellianada; Kurniawan, Dani; Agustin, Indri; Winarni, Arik Muji; Tripriyono, Setiyo Budi; Muhammady, Maghfur El; Qomariah, Nurul; Nursaid, Nursaid; Mu’ah, Mu’ah (International Journal of Management Science and Information Technology, 2025)
This study aims to describe customer satisfaction based on the marketing mix strategy (7Ps) which includes product, price, place, promotion, people, process, and physical evidence at PT Tirta Perkasa Sejahtera Bondowoso. This study uses a qualitative approach with a descriptive research type. Data were obtained through in-depth interviews, direct observation, and documentation related to the company's service and marketing activities. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results show that the marketing mix strategy (7Ps) has been consistently implemented by the company and contributes to the level of customer satisfaction. Customers consider product quality, ease of service access (place), and fast and responsive service processes to be the aspects that most influence their satisfaction. Meanwhile, the promotion strategy and physical evidence elements are considered to still have room for improvement to strengthen the overall customer experience. This study provides an in-depth overview of how the implementation of the 7Ps can increase customer satisfaction and serve as a reference for improvement for companies in designing more effective marketing strategies.